Dietary Variety Is Inversely Associated with Body Adiposity among US Adults Using a Novel Food Diversity Index. Issue 3 (31st December 2014) - Vadiveloo, Maya; Dixon, L Beth; Mijanovich, Tod; Elbel, Brian; Parekh, Niyati
Abstract: Background: Consuming a variety (vs. monotony) of energy-poor, nutrient-dense foods may help individuals adhere to dietary patterns favorably associated with weight control. Objective: The objective of this study was to examine whether greater healthful food variety quantified using the US Healthy Food Diversity (HFD) index favorably influenced body adiposity. Methods: Men and nonpregnant, nonlactating women aged ≥20 y with two 24-h recalls from the cross-sectional NHANES 2003–2006 ( n = 7470) were included in this study. Dietary recalls were merged with the MyPyramid Equivalent database to generate the US HFD index, which ranges from 0 to ∼1, with higher scores indicative of diets with a higher number and proportion of healthful foods. Multiple indicators of adiposity including BMI, waist-to-height ratio, android-to-gynoid fat ratio, fat mass index (FMI), and percentage body fat were assessed across US HFD index quintiles. ORs and 95% CIs were computed with use of multivariable logistic regression (SAS v. 9.3). Results: The US HFD index was inversely associated with most adiposity indicators in both sexes. After multivariable adjustment, the odds of obesity, android-to-gynoid ratio >1, and high FMI were 31–55% lower ( P -trend < 0.01) among women in quintile 5 vs. quintile 1 of the US HFD index. Among men, the odds of obesity, waist-to-height ratio ≥0.5, and android-to-gynoid ratio >1 were 40–48% lower ( P -trend ≤ 0.01) in quintile 5 vs. quintile 1 of the US HFD index. Conclusions: Higher US HFD index values were inversely associated with indicators of body adiposity in both sexes, indicating that greater healthful food variety may protect against excess adiposity. This study explicitly recognizes the potential benefits of dietary variety in obesity management and provides the foundation to support its ongoing evaluation.